The strange library [compact disc, unabridged] - Murakami, Haruki, 1949- (Books on Tape ; Random House Audio, 2014)
A boy visits a library on his way home from school. An old man takes the boy hostage and forces him to memorize a large number of books. The boy eventually realizes that the man plans to absorb the information he's memorized by eating his brain. With the help of a strange girl and a man dressed as a sheep, the captive devises an escape plan.